Interaction of Trappist-1 exoplanets with coronal mass ejections: Joule heating, Poynting fluxes, and the role of magnetic fields - Elekes, Filip; Saur, Joachim; Grayver, Alexander (Astronomy and astrophysics (Berlin), 2025)
Context . Flares and associated coronal mass ejections (CMEs) are energetic stellar phenomena that drastically shape the space weather around planets. Close-in exoplanets orbiting active cool stars are likely exposed to particularly extreme space weather, and the effects on the planets are not understood well enough. The terrestrial Trappist-1 exoplanets are excellent subjects to study the impact of CMEs on close-in planetary bodies, their atmospheres and ultimately their habitability. Aims . Our aim is to better understand the role of planetary magnetic fields in shielding the planet energetically from external forcing. We expand on recent studies of CME-induced Joule heating of planetary interiors and atmospheres by including a magnetohydrodynamic (MHD) model of the interaction. Methods . We studied the interaction of CMEs with Trappist-1b and e using time-dependent MHD simulations. We considered magnetic flux rope and non-magnetized DP CMEs. We calculated induction heating in the planetary interior and ionospheric Joule heating for various intrinsic magnetic field strengths and CME energies. Results . Magnetospheric compression is the main driver of magnetic variability. Planetary magnetic fields enhance induction heating in the interior, although the effect is weaker with flux rope CMEs. Single event dissipation rates with 1-hour CMEs amount to 20 TW and 1 TW for Trappist-1b and e, respectively. Taking into account CME occurrence rates, the annual average heating rates are ≈10 TW (b) and 1 TW (e), which are placed near the lower end of previously estimated dissipation rates. Within the range of the studied planetary magnetic field strengths, B p , magnetospheric inward Poynting fluxes scale with B 3 p . Thus, stronger magnetic fields increase the absorption of CME energy. Ionospheric Joule heating rates amount to 10 3-4 TW and decrease for stronger magnetic fields, B p . These heating rates exceed the average stellar XUV input by one to two orders of magnitude and might severely impact atmospheric erosion. In a steady state, stellar wind ionospheric Joule heating amounts to ≈10 2 TW.